2013
DOI: 10.1149/05201.0495ecst
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of Recent Advances in Chemical Mechanical Polishing (CMP) of Sapphire Substrates

Abstract: Nowadays, sapphire substrates are widely employed for GaN light emitting diodes (LEDs) due to their comparatively low cost, large diameter, high quality, optical transparency, and high temperature stability etc. However, in spite of its commercial importance and extended history, the machining of sapphire remains a challenge. In the manufacture of sapphire, chemical mechanical polishing (CMP) has been widely used to obtain a mirror surface on the sapphire substrate and minimize the subsurface damages. In this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…Thus, reclaiming the sapphire substrate for GaN-based LED wafers can significantly reduce the manufacturing cost of LED chips. A chemical mechanical polishing (CMP) method is currently used universally to reclaim substrates [8][9][10]. However, the disadvantages of CMP include process complexity, surface scrapes, and thinning of the sapphire substrate.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, reclaiming the sapphire substrate for GaN-based LED wafers can significantly reduce the manufacturing cost of LED chips. A chemical mechanical polishing (CMP) method is currently used universally to reclaim substrates [8][9][10]. However, the disadvantages of CMP include process complexity, surface scrapes, and thinning of the sapphire substrate.…”
Section: Introductionmentioning
confidence: 99%
“…In the recent years, the demand for light emitting diodes (LEDs) continue to rise because LEDs can reduce energy consumption when compared with conventional light sources. In the fabrication process of LEDs, sapphire material is an ideal material because of its relatively low cost, large attainable diameter, chemical compatibility, optical transparency and high temperature stability (Yu-Nong Zhang, et al, 2013). In addition, sapphire crystal structure is preferable for LED lights efficiency in order to have a wider beam angle and a structure similar to that of gallium nitride (GaN).…”
Section: Introductionmentioning
confidence: 99%
“…3 Many efforts have been carried out to improve the polishing performance of sapphire CMP. [4][5][6][7] Shi et al 8 compared the polishing effect of alumina abrasives and silica abrasives during the sapphire CMP process. The results indicated that soft spherical silica abrasive particles could achieve good surface quality.…”
mentioning
confidence: 99%